Who Is Nicholas Stanford?: The New York Times Music Critic and His Secret Role in the Rise of the "Liberal Media" Claim. Issue 4 (2nd October 2018) - Bedingfield, Sid
Abstract : In 1955, New York Times music critic John Briggs joined forces with a southern newspaper editor to launch a secret campaign against "liberal" bias in the northern media. While still working for the Times, Briggs wrote columns for the Charleston News and Courier under the pseudonym "Nicholas Stanford." This study argues that Briggs's work for the Charleston newspaper helps fill a gap in the literature concerning the "liberal media" claim and its role in the rise of the conservative political movement. It shows how the Brown ruling fueled the "liberal media" claim in the South. It also contends that conservatives employed the attack line successfully to undermine the claim of objectivity, a core tenet of the professionalized journalism that emerged in the twentieth century.